Acute anticholinergic syndrome due to Datura innoxia Miller mixed with lime tea leaves - Pekdemir, M; Yanturali, S; Akay, S; Alagoz, G (Comparative Toxicology Lab, 2004)
Anticholinergic plants contain a variety of alkaloids and have been used for herbal medications. We present a case of acute anticholinergic syndrome from ingestion of lime tea accidentally mixed with Datura Innoxia Miller. Its intoxication should be suspected in patients presenting with altered mental status, agitation and hallucinations and with other anticholinergic symptoms and signs. Toxicities of herbal medicine should always be considered and queried when a patient presents with unusual systemic symptoms.
Keywords: Physostigmine; Stramonium; Ingestion; Trumpet